2009
DOI: 10.1038/cmi.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces T-cell apoptosis by inhibiting chemokine C receptor 7 expression: the role of adenosine receptor A2

Abstract: Hypoxia is a major characteristic of the tumor microenvironment, and its effects on immune cells are proposed to be important factors for the process of tumor immune escape. It has been reported that hypoxia affects the function of dendritic cells and the antitumor function of T cells. Here we discuss the effects of hypoxia on T-cell survival. Our results showed that hypoxia induced apoptosis of T cells. Adenosine and adenosine receptors (AR) are important to the hypoxia-related signaling pathway. Using AR ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…Culturing at low pO 2 (5% O 2 ) did not change the percent of viable cells, which agrees with previous data [1]. Other investigators revealed increased viability of lymphocytes under condition of hypoxia [12,15] and induction of apoptosis in T lymphocytes under conditions of reduced O 2 content [16]. It is known that MMSC maintain viability of both non-activated [4] and activated lymphocytes [18].…”
Section: Resultssupporting
confidence: 72%
“…Culturing at low pO 2 (5% O 2 ) did not change the percent of viable cells, which agrees with previous data [1]. Other investigators revealed increased viability of lymphocytes under condition of hypoxia [12,15] and induction of apoptosis in T lymphocytes under conditions of reduced O 2 content [16]. It is known that MMSC maintain viability of both non-activated [4] and activated lymphocytes [18].…”
Section: Resultssupporting
confidence: 72%
“…Adenosine strongly impairs development of effector T cells, especially those that produce IFN-γ and are cytotoxic to tumor cells [84]. Sun et al reported that hypoxia can induce T-cell apoptosis through adenosine/adenosine (2) receptor signaling in vitro [85]. Cytotoxic activity by NK cells is also restrained by hypoxia.…”
Section: Immunosuppression After Anti-vegf Therapy By Increased Tumormentioning
confidence: 99%
“…Hypoxia was shown to decrease T-cell survival (29), and incubation of na€ ve T cells under hypoxia decreases their secretion of the trophic cytokine IL2 in a HIF1-dependent manner (30). CD4 þ and CD8 þ T cells derived from HIF1a-deficient mice exhibit increased proliferation, produce higher levels of interferon-g, and display increased antitumor responses (31).…”
Section: Direct Effects Of Hypoxia On Immune Effectorsmentioning
confidence: 99%